Pengelolaan Iklim Komunikasi Organisasi dalam Memperbaiki Motivasi Kerja: (Studi Kasus pada Store Charles and Keith Summarecon Mall Serpong) - Lola Amelia Putri Eduard; Agung Putra Mulyana (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
Organizational Communication Climate Mangement in Improving Charles & Keith Employee Work Motivation (Case Study at Charles & Keith Store Summarecon Mall Serpong). Organizational communication climate is a key element in creating a productive work environment, especially in the dynamic retail industry. This study aims to describe the organizational communication climate formed at the Charles and Keith Store Summarecon Mall Serpong and to determine the level of employee work motivation at the Charles and Keith Store Summarecon Mall Serpong. This study was conducted at the Charles & Keith Store located in Summarecon Mall Serpong, Tangerang for 3 months, starting from April to June 2025 using a qualitative approach with a case study method, involving in-depth interview observations, and documentation of data collection techniques. The results of the study indicate that a warm, supportive, and transparent communication climate plays a vital role in creating a healthy and inspiring work atmosphere. Employees feel valued because they are given space to express their opinions, are involved in decision-making, and receive honest and constructive feedback. In addition, trust and honesty are important foundations in building harmonious and work-oriented working relationships. These findings emphasize that good communication climate management has a direct impact on employee morale, loyalty, and productivity in the modern retail sector.